META-RESEARCH OF KOMUNITAS PENGKAJI KOMUNIKASI: MAINSTREAMING ALTERNATIVE FIELDS AMIDST INDONESIA COMMUNICATION ACADEMIA - Purwandi, Edeliya Relanika; Safitri, Reza (LPPM Institut Pendidikan Nusantara Global, 2023)
This research recommends meta-research as one of propitious research methods in mainstreaming the alternative fields amidst Indonesia’s communication academia. Our thesis came from the scrutiny of Komunitas Pengkaji Komunikasi (KPK) intellectual activism. It questioned and intervened the lacking alternative fields within Indonesia’s communication scholarships. We analyzed 48 documents from varying of KPK’s research publications related to the epistemological cues for knowing the verstehen worldview of KPK’s intellectual craftsmen. Harnessing Miles, Huberman & Saldana’s interactive analysis method, our findings reiterated on how KPK alternative fields development had embraced unorthodox research outputs. KPK also had closely enquired an inclusive interparty collaboration. KPK also enforced the research and advocacy endeavours. Yet reflecting from 48 document findings, we expected for more rigorous literature studies of the extended field of interests. We end by calling for larger Indonesian communication scholars to enforce field diversity against the saturated fields, likened to what KPK has endured insofar.